Worker Handyman Solutions - Siddhant Rai; Mohit Kalwar; Swatantra Yadav; Prof. Aabha Patil; Vipin Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The goal of the "Worker Handyman Solutions: Providing Reliable Home Services" initiative is to employ an innovative online platform to improve the dependability and accessibility of home maintenance services. The project’s goal is to design an intuitive user interface that will allow clients to quickly and easily specify what they need from a range of home services. Through the use of cutting-edge technology, the platform links clients with qualified professionals, guaranteeing reliable and timely solutions for a variety of jobs. The principal aims of this initiative are to optimize the hiring process, boost client contentment, and facilitate effective correspondence between service recipients and suppliers. By providing clients with a dependable, customized , and easy-to-use solution, the team hopes to transform the home services sector and enhance their overall home maintenance experience.